2013
DOI: 10.4137/bic.s11475
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Apoptosis Pathway in Colorectal Cancer: A Review of the Literature on Biomarkers Identified by Immunohistochemistry

Abstract: Research towards biomarkers that predict patient outcome in colorectal cancer (CRC) is rapidly expanding. However, none of these biomarkers have been recommended by the American Association of Clinical Oncology or the European Group on Tumor Markers. Current staging criteria result in substantial under-and over-treatment of CRC patients. Evasion of apoptosis, a characteristic feature of tumorigenesis, is known to correlate with patient outcome. We reviewed the literature on immunohistochemistry-based studies b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 152 publications
(210 reference statements)
2
55
0
4
Order By: Relevance
“…The most important members of this family are Bcl-XL and Bax proteins [14,15]. Deregulation of apoptosis during tumor development can be caused by a disturbance in the homeostatic balance of the Bcl-2 family members [16]. Specially, Bcl-XL is overexpressed in colorectal cancers and knockdown of this protein could suppress the growth of rectal cancer xenografts derived from patient tumors [17].…”
Section: Discussionmentioning
confidence: 99%
“…The most important members of this family are Bcl-XL and Bax proteins [14,15]. Deregulation of apoptosis during tumor development can be caused by a disturbance in the homeostatic balance of the Bcl-2 family members [16]. Specially, Bcl-XL is overexpressed in colorectal cancers and knockdown of this protein could suppress the growth of rectal cancer xenografts derived from patient tumors [17].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of researches show that human peripheral blood lymphocytes hypoxantine-guanine phpsphoribosyl transferase (HPRT) gene, which is a chemical and ionizing radiation sensitive mutagen loci (Nicklas et al, 1991;Zimmer et al, 1997;Hamdan et al, 1999;Helleday et al, 2000), was closely related to the p53 and bcl-2 gene (Liu et al, 1997;Phillips, Gebow et al, 1997), which had been demonstrated strongly association with cancer development (Murray et al, 2012;Zeestraten et al, 2013),especially with breast cancer and esophageal cancer (Bellini et al, 2012;Walerych et al, 2012). Therefore, it is worthy to emphasize that the occupational X-ray radiation exposure might interact with phosphoribosyl gene mutation contribute to cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, the study presented here is the first study combining methylation data of several apoptosis genes at the same time, based on their functions in the intrinsic apoptotic process [48]. The methylation percentages of the combined markers Apaf1, Bcl2 and p53 correlated significantly with the apoptotic status of the tumors (M30 IHC staining) and disease outcome (patient survival and disease recurrence).…”
Section: Discussionmentioning
confidence: 99%